COMMITTEE OF REGIONS OF THE EUROPEAN UNION IMPACTING LOCAL GOVERNANCE PERFORMANCE THROUGH REGIONAL INITIATIVES - Qejvani, Olta; Lirëza, Linert (International Journal of Legal and Social Order, 2025)
A key organization in the European Union that represents municipal and regional governments is the Committee of Regions (CoR). It uses a number of regional efforts to significantly influence how local governance functions. In the EU policymaking process, the CoR represents the interests of cities and regions. It guarantees that local and regional leaders' opinions are heard regarding laws that impact local governance. The Committee plans training sessions, seminars, and workshops to enhance local governments' capabilities. Through these programs, local authorities are able to acquire the knowledge and abilities necessary for efficient implementation of regional development context. The organization itself influences EU financing programs like the European Regional Development Fund (ERDF). The CoR ensures that financial resources are allocated to projects that enhance local infrastructure and governance by exerting influence over the allocation process. Additionally, it encourages municipal authorities to involve individuals in decision-making processes by promoting participatory governance models. Through these initiatives, the Committee of Regions significantly enhances the performance of local governance in the EU. By advocating for local interests, facilitating knowledge exchange and promoting capacity building, the CoR aims ensuring that regional authorities have the proper capacities to meet the challenges they face and improve the quality of life for their citizens. This paper aims to investigate the role of the CoR in local governance through the instrument of regional initiatives. It begins with an overview of the institution's structure, analyzes the regional initiatives that have been successfully implemented thus far and delves deeper into the ways in which the CoR works with other EU institutions to enhance regional initiatives. After conducting a qualitative investigation on the Lisbon Treaty and Committee of Regions web data, our final goal is to pinpoint the creative advancements that this organization has made that have strengthened local governance while also outlining potential further initiatives.